Extensive eccentric contractions in intact cardiac trabeculae: revealing compelling differences in contractile behaviour compared to skeletal muscles. Issue 1903 (29th May 2019) - Tomalka, André; Röhrle, Oliver; Han, June-Chiew; Pham, Toan; Taberner, Andrew J.; Siebert, Tobias
Abstract : Force enhancement (FE) is a phenomenon that is present in skeletal muscle. It is characterized by progressive forces upon active stretching—distinguished by a linear rise in force—and enhanced isometric force following stretching (residual FE (RFE)). In skeletal muscle, non-cross-bridge (XB) structures may account for this behaviour. So far, it is unknown whether differences between non-XB structures within the heart and skeletal muscle result in deviating contractile behaviour during and after eccentric contractions. Thus, we investigated the force response of intact cardiac trabeculae during and after isokinetic eccentric muscle contractions (10% of maximum shortening velocity) with extensive magnitudes of stretch (25% of optimum muscle length). The different contributions of XB and non-XB structures to the total muscle force were revealed by using an actomyosin inhibitor. For cardiac trabeculae, we found that the force–length dynamics during long stretch were similar to the total isometric force–length relation. This indicates that no (R)FE is present in cardiac muscle while stretching the muscle from 0.75 to 1.0 optimum muscle length. This finding is in contrast with the results obtained for skeletal muscle, in which (R)FE is present. Our data support the hypothesis that titin stiffness does not increase with activation in cardiac muscle.